2020
DOI: 10.3389/fonc.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Linc00668 Promotes Invasion and Stem Cell-Like Properties of Breast Cancer Cells by Interaction With SND1

Abstract: Long non-coding RNAs (lncRNAs) are reported to be involved in breast cancer progression. Herein, we observed that the expression of Linc00668 was increased in breast cancer compared to normal tissue. The patients with high Linc00668 expression exhibited an association with a higher metastatic risk. We demonstrated that forced expression of Linc00668 enhanced, whereas depletion of Linc00668 diminished invasion and self-renewal of breast cancer cells as well as resistance to doxorubicin (Dox). Further mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Numerous studies have reported LncRNAs’ functions in tumor progression depended on their interaction with RNA-binding proteins (RBPs) ( 7 , 22 ). We also seek to identify the RBPs could physically interact with LINC00467 and mediate its oncogenic role in breast cancer progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported LncRNAs’ functions in tumor progression depended on their interaction with RNA-binding proteins (RBPs) ( 7 , 22 ). We also seek to identify the RBPs could physically interact with LINC00467 and mediate its oncogenic role in breast cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), a class of RNA molecules longer than 200 nucleotides, with less protein-coding capacity, have been reported to play crucial roles in multiple cellular processes, tumor progression included (4)(5)(6). In general, LncRNAs function via interacting with proteins, chromatin DNA or other types of RNAs to mediate their stability or activity in different aspects of tumor biology (7)(8)(9)(10). LINC00467 (ID in NCBI database: 84791), a LncRNA has attracted much attention recently, was reported to be dysregulated in spermatogenesis and male infertility (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…212 lncRNA LINC00668 is upregulated in breast cancer cells and improves DOX resistance by targeting staphylococcal nuclease domain-containing 1 (SND1). 213 Contrary to positive regulation of above lncRNAs in breast cancer resistance to anthracycline, some lncRNAs can reduce the drug resistance. lncRNA PTENP1 is downregulated in breast cancer cells and tissues.…”
Section: Lncrnas Mediate Breast Cancer Invasion and Metastasismentioning
confidence: 99%
“… 212 lncRNA LINC00668 is upregulated in breast cancer cells and improves DOX resistance by targeting staphylococcal nuclease domain-containing 1 (SND1). 213 …”
Section: The Role Of Lncrna In Breast Cancer Malignant Progressmentioning
confidence: 99%
“…It has been reported that there is a correlation between linc00668 upregulation and lymph node metastasis in BC patients. Linc00668 induces cell invasion, self-renewal properties, and DOX resistance in BC cells through SND1 binding to upregulate SMAD2/3/4 [ 54 ].…”
Section: Introductionmentioning
confidence: 99%